Local Knowledge and Adaptive Strategies of Farmers to Deal with Spodoptera Frugiperda in Corn: Pengetahuan Lokal Dan Strategi Adaptif Petani Menghadapi Spodoptera Frugiperda Pada Jagung - Yulia Oliviana Gaib (Universitas Widya Gama Mahakam, 2025)
Spodoptera frugiperda (FAW) is the main threat to the early vegetative phase of corn in North Gorontalo. This research aims to develop a typology of adaptive strategies based on local knowledge, serving as the foundation for contextual and affordable PHT recommendations. The qualitative approach is employed through a combination of focused ethnography, Participatory Rural Appraisal (PRA), and Grounded Theory analysis. Data were collected in three sub-districts (Kwandang, Gentuma Raya, Atinggola) through 28 in-depth interviews, 7 FGDs, 5 PRA sessions, and 9 farm-walks with purposive snowball sampling. The results indicate the presence of a